(untitled) (Computer systems and information technologies, 2024)
Based on the postulate that the arms trade is generally a complex, specific and multifaceted field of activity, which includes the production, distribution, sale and use of various types of weapons and military equipment. In this context, the authors of the article proposed the development of an innovative information technology platform for accounting and analysis of arms trade processes, which takes into account the peculiarities of domestic legislation. It was noted that the use of blockchain technology on the information and technological platform of weapons sales is aimed at increasing security and tracking the full set of transactions, reducing risks and ensuring maximum transparency of processes. It is assumed that each stage of the life cycle of weapons, starting from design, production and ending with sale, will be recorded by blockchain methods and means. Information about the manufacturer, the date of manufacture, transportation, purchase and acceptance of the weapon by the customer will be recorded in the blocks. With the use of an information technology platform, the validity of licenses will be checked with each transaction, ensuring the legality of the sale and taking into account the unique characteristics of each weapon unit. The information technology platform will store information about transactions, including price, date and participants, smart contracts, etc. Development of an information technology platform that is conveniently integrated into the system of international standards and regulators, as well as meets numerous specific requirements and restrictions on arms trade. The authors of the article claim that the use of cryptography in blockchain technology provides reliable encryption and protection of confidential information, which is critical in a sensitive subject area such as the arms trade, and also contributes to a significant increase in the level of security, transparency and trust among participants in this specific industry. The conducted analysis confirms the expediency of using the potential of blockchain technology to optimize and increase the efficiency of the accounting of arms trade processes, as well as to ensure the reliability and safety of the functioning of the innovative information technology platform.